Responsive Research and Scientific Autonomy - Leonelli, Sabina (NOvation — Critical Studies of Innovation, 2024)
Von Schomberg’s call to place mutual responsiveness – which I understand as the ability of researchers and the research system as a whole to foster meaningful exchanges and learn from novel experiences, no matter where those originate – at the core of Open Science and related efforts to reform the scientific landscape is both timely and significant. Widespread sharing is not enough to guarantee responsible and inclusive research, nor are vague appeals to improve research culture, whatever it is that such culture may turn out to include (Leonelli, 2023). Rather, emphasis needs to be placed on the conditions under which sharing materials, methods and insights – and debating the goals and directions towards which these may be put to use – may improve research exchange, communication and scrutiny, resulting in scientific outputs that are both reliable and socially responsive. Hence von Schomberg’s focus on the interplay between institutional and behavioural features of science and his plea for a reform in governance structures, such as initiated by COARA, are very well-taken. He is, however, too quick to dismiss the importance of some degree of autonomy for those involved in creating knowledge. To show why this matters, I here briefly discuss two of von Schomberg’s additional claims: (1) his focus on ‘knowledge actors’ as the protagonists of research efforts; and (2) his critique of the effectiveness of self-governance efforts by researchers.